2013
DOI: 10.1088/1741-2560/10/3/036001
|View full text |Cite
|
Sign up to set email alerts
|

Cervical intraspinal microstimulation evokes robust forelimb movements before and after injury

Abstract: Objective Intraspinal microstimulation (ISMS) is a promising method for reanimating paralyzed limbs following neurological injury. ISMS within the cervical and lumbar spinal cord is capable of evoking a variety of highly-functional movements prior to injury, but the ability of ISMS to evoke forelimb movements after cervical spinal cord injury is unknown. Here we examine the forelimb movements and muscles activated by cervical ISMS both before and after contusion injury. Approach We documented the forelimb mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 29 publications
8
83
0
1
Order By: Relevance
“…Currently, data on the effects of epidural stimulation to neuromodulate the cervical cord chronically are non-existent. Previous work in the rats has shown that instraspinal stimulation of the cervical segments of the spinal cord in rats elicits motor responses in multiple forelimb muscles (Sunshine et al, 2013) and selected stimulation parameters can facilitate functional reaching and grasping movements in monkeys (Zimmermann et al, 2011; Sharpe and Jackson, 2014). Chronic intraspinal stimulation of the spinal cord has been reported to improve forelimb function in SCI rats (Kasten et al, 2013; Mondello et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, data on the effects of epidural stimulation to neuromodulate the cervical cord chronically are non-existent. Previous work in the rats has shown that instraspinal stimulation of the cervical segments of the spinal cord in rats elicits motor responses in multiple forelimb muscles (Sunshine et al, 2013) and selected stimulation parameters can facilitate functional reaching and grasping movements in monkeys (Zimmermann et al, 2011; Sharpe and Jackson, 2014). Chronic intraspinal stimulation of the spinal cord has been reported to improve forelimb function in SCI rats (Kasten et al, 2013; Mondello et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that intraspinal stimulation at the cervical segments of the spinal cord elicits motor responses in multiple forelimb muscles in rats (Sunshine et al, 2013) and that selected stimulation parameters can facilitate functional reaching and grasping movements in non-injured monkeys (Zimmermann et al, 2011; Sharpe and Jackson, 2014). It also has been shown that chronic intraspinal stimulation at the cervical spinal cord can improve forelimb function in rats with a cervical SCI (Kasten et al, 2013; Mondello et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A cSCI between C5 and C7 leads to minimal loss of control of the elbow flexors, but to disrupted voluntary control of the elbow extensors (Maynard et al, 1997;Sunshine et al, 2013), which give a unique opportunity to investigate changes in the activation of agonist and antagonist muscles Wiegner, 1992, 1996). Given that the signals from peripheral afferents and descending pathways may considerably differ between cSCI and healthy participants during actual contractions (Boorman et al, 1996), comparisons at both similar percentages of the maximal net torque and absolute net torques allow an evaluation of the mechanisms underlying the performance, as opposed to performance itself.…”
Section: Introductionmentioning
confidence: 99%